Dinamika Bahasa Indonesia dalam Konteks Pengelolaan Perkantoran - Laudhita, Nazla; Ananta, ⁠Edra Aurelia; Pashadea, ⁠Raisya; Lestari, ⁠Aprilia Tri; Imani, ⁠Dzahabi Nuro; Rizkyanfi, ⁠Mochamad Whilky (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the dynamics that occur in offices in the use of Indonesian. This study uses qualitative interview method for Indonesian dynamics in the context of office management. Three interviewees from the office environment were interviewed to understand their views and experiences regarding the role of Indonesian. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusions. . The results of data analysis confirm that although in the office world there is already an influence from technology, Indonesian remains the main choice for communicating in the office world, without reducing the quality and diversity of Indonesian. Improve Indonesian language skills to improve communication efficiency in the workplace. The study also highlights the importance of practicing good and correct Indonesian in the office world, as it reflects professionalism and increases trust in communication. Therefore, this study highlights the need for attention to the use of good and correct Indonesian in the office environment to create effective and professional communication